Physico-chemical characteristics, nutritional quality, and oxidative stability of cold-pressed chia seed oil, date palm seed oil, along with their binary mixtures - Rehab F. M. Ali; Ayman M. El-Anany (Cogent Food & Agriculture)
The current study aimed to investigate the effects of mixing chia seed oil (CSO) and date palm seed oil (DPSO) on the physico-chemical properties, nutritional quality, along with oxidative stability of the resulting binary mixtures.. A70:30 blend of CSO and DPSO shows a ΣMUFA content 2.11 times higher than pure CSO, with a ΣPUFA content 1.40 times lower. The incorporation of DPSO improves the oxidative stability of CSO, with reductions in COX values from 1.10 to 1.39. Blends exhibit a reduction in the atherogenic index by 87.5%–68.33% and a decrease in the thrombogenic index by 8.18–3.19 times. The total phenolic content increases with DPSO incorporation, enhancing the antioxidant properties of the blends by 1.31–1.91 times compared to CSO alone. Blends with 30%, 25%, and 20% DPSO exhibited lower acid values by factors of 1.24, 1.18, and 1.13, respectively, compared to pure CSO. After 90 days, the peroxide values of the blends were lower by factors of 2.00, 1.25, and 1.22 compared to pure CSO. The TBA values showed reductions of 1.53, 1.35, and 1.24 for the respective blends. The induction periods increased by 3.68, 3.17, and 2.75 times for the blends, demonstrating enhanced resistance to oxidative degradation.